2011
DOI: 10.1007/s10059-011-0071-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antioxidants on the Production of Pro-Inflammatory Cytokines and Orthodontic Tooth Movement

Abstract: Orthodontic force causes gradual compression of the periodontal ligament tissues, which leads to local hypoxia in the compression side of the tissues. In this study, we investigated whether antioxidants exert a regulatory effect on two factors: the expression of pro-inflammatory cytokines in human periodontal ligament fibroblasts (PDLFs) that were exposed to mechanical compression and hypoxia and the rate of orthodontic tooth movement in rats. Exposure of PDLFs to mechanical compression (0.5-3.0 g/cm 2 ) or hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Furthermore, previous study confirmed that hypoxia increased the expression of the proinflammatory cytokines such as interleukin- (IL-) 1 β , IL-6, IL-8, VEGF, and tumor necrosis factor- α (TNF- α ). These proinflammatory cytokines play an important role in orthodontic tooth movement through regulation of matrix metalloproteinase expression and osteoclast differentiation [ 25 , 26 ]. In our experiment, we can observe the initial inflammatory cells inside the blood vessels in the pulp tissue at 1 d and 3 d, such as neutrophils, eosinophils, and monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous study confirmed that hypoxia increased the expression of the proinflammatory cytokines such as interleukin- (IL-) 1 β , IL-6, IL-8, VEGF, and tumor necrosis factor- α (TNF- α ). These proinflammatory cytokines play an important role in orthodontic tooth movement through regulation of matrix metalloproteinase expression and osteoclast differentiation [ 25 , 26 ]. In our experiment, we can observe the initial inflammatory cells inside the blood vessels in the pulp tissue at 1 d and 3 d, such as neutrophils, eosinophils, and monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…11 Moreover, treatment of the inhibitor of HIF-1a suppressed the rate of tooth movement. 12 These findings illustrate that oxygen tension might be involved in osteoclastogenesis during OTM.…”
Section: Introductionmentioning
confidence: 81%
“…A rat model of orthodontic tooth movement which consumed anti oxidants Resveratrol or N-acetylcysteine. 34 It suppressed the expression of proinflammatory cytokines interleukin-1β and tumor necrosis factor-α in the periodontal ligament tissues compared to the vehicletreated group, thus inhibit bone resorption and retard OTM. Consumption of pomegranate extract accelerate bone formation.…”
Section: Discussionmentioning
confidence: 99%